2004
DOI: 10.1023/b:neon.0000013474.01161.58
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 and Matrix Metalloproteinase-9 Expressions Correlate with the Recurrence of Intracranial Meningiomas

Abstract: Our study indicated that MMP-2 and MMP-9 expressions are prognostic factors predicting the recurrence of meningioma, independent of proliferative potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 24 publications
5
44
2
2
Order By: Relevance
“…MMP2 was generally very highly or highly expressed. This finding is consistent with previous reports suggesting their association with the potential to invade, especially increased levels of MMP2 and MMP9 in Grade 1 meningiomas as prognostic or predictive factors of recurrence (16,32). Moreover, in another study, the prognostic value of MMP9 in the risk of recurrence of meningiomas was investigated by analysing its expression in a series of meningiomas of different histological type and grade.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…MMP2 was generally very highly or highly expressed. This finding is consistent with previous reports suggesting their association with the potential to invade, especially increased levels of MMP2 and MMP9 in Grade 1 meningiomas as prognostic or predictive factors of recurrence (16,32). Moreover, in another study, the prognostic value of MMP9 in the risk of recurrence of meningiomas was investigated by analysing its expression in a series of meningiomas of different histological type and grade.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, MMP2 was also very highly expressed in all the snap frozen tissue samples (samples [13][14][15][16][17] and the majority of cultured cells (samples 1-12) whereas MMP9 was only highly expressed in 5 of the latter group (Fig. 1).…”
Section: Differential Expression Of Mmps and Timps In 17 Meningiomasmentioning
confidence: 92%
See 1 more Smart Citation
“…In human beings, 23.2% and 39.3% of meningiomas are reported to show a high expression of MMP-2 and MMP-9, respectively. 33 Whether the sample was taken as a biopsy or at necropsy does not seem to play a role in MMP-2 and MMP-9 expression either, suggesting that sampling time (in life or postmortem) is not a sufficient criterion to consider the biologic stage of the tumor. In fact, in our experience necropsy material does not always indicate the tumor with the most severe biologic behavior, because owners may request euthanasia because of a dramatic clinical progression or as soon as a cancer is diagnosed, thereby refusing support therapy or feasible surgery.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 In our study we found that metalloproteinase expression is also independent of proliferative potential, as commonly observed in human meningiomas. 33 Only recently, a positive correlation was found between MMP-9 expression and proliferative index. 34 The proliferative index failed to be assessed by Ki67 expression in a number of cases, most likely due to a prolonged storage in formalin or in paraffin blocks responsible for subcellular modifications.…”
Section: Discussionmentioning
confidence: 99%